2020
DOI: 10.22271/phyto.2020.v9.i1am.10818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated weed management on growth parameters and yield attributes of Indian mustard (Brassica juncea L.)

Abstract: A field experiment was conducted with ten treatments pendimethalin (PE) @1.0kg ha -1 , isoproturon (POE) @1.20kg ha -1 , pendimethalin (PE) @1.0kg ha -1 +hand weeding at 45 DAS, isoproturon (POE) @1.20kg ha -1 +hand weeding at 45 DAS, pendimethalin (PE) @1.0kg ha -1 +straw mulch @5t ha -1 , isoproturon (POE) @1.20kg ha -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Sharma et al [39] noticed that weed free treatment resulted in the highest yield attributes like number of siliquae plant -1 , number of seeds siliquae -1 and number of secondary branches plant -1 significantly which was followed by pendimethalin 38.7 CS @ 0.75 kg ha-1 + HW 30 DAS and pendimethalin 30 EC @ 0.75 kg ha -1 + HW 30 DAS respectively. Raj et al [70] revealed that two hand weeding at 20 and 40 DAS gave higher plant height, dry matter accumulation in g/plant, leaf area index and number of primary and secondary branches/plant. It was at par with pendimethalin (PE) 1.0 kg/ha + straw mulch 5 t/ha.…”
Section: Effect Of Weed Management Practices On Crop Growth Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma et al [39] noticed that weed free treatment resulted in the highest yield attributes like number of siliquae plant -1 , number of seeds siliquae -1 and number of secondary branches plant -1 significantly which was followed by pendimethalin 38.7 CS @ 0.75 kg ha-1 + HW 30 DAS and pendimethalin 30 EC @ 0.75 kg ha -1 + HW 30 DAS respectively. Raj et al [70] revealed that two hand weeding at 20 and 40 DAS gave higher plant height, dry matter accumulation in g/plant, leaf area index and number of primary and secondary branches/plant. It was at par with pendimethalin (PE) 1.0 kg/ha + straw mulch 5 t/ha.…”
Section: Effect Of Weed Management Practices On Crop Growth Parametersmentioning
confidence: 99%
“…Maximum seed and stover yield and harvest index of mustard were noticed under two hand weeding at 20 and 40 DAS followed by pendimethalin (PE) 1 kg ha -1 + hand weeding at 30 DAS [38]. Raj et al [70] reported that, maximum seed, stover yield and harvest index were observed with application of pendimethalin (PE) 1 kg ha -1 + straw mulch 5t ha -1 followed by two hand weedings at 20 and 40 DAS in mustard. Sharma et al [39] observed that among the treatments, pre-emergence application of pendimethalin 38.7 CS @ 0.75 kg ha-1 + HW 30 DAS recorded higher seed yield, straw yield and biological yield (1220, 5549 and 6769 kg ha -1 ) next to weed free treatment (1297, 5888 and 7185 kg ha -1 ).…”
Section: Yieldmentioning
confidence: 99%
“…Mustard oil is used as condiment in pickles, flavouring curries and vegetables, preparation of hair oils, medicines, soap making and in the tanning industry for softening of leather. The mustard cake is used mostly for cattle feed and manure" [2].…”
Section: Original Research Articlementioning
confidence: 99%